The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.18502/ijm.v13i2.5976
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors, bacteriological profile and outcome of surgical site infections following orthopaedic surgery

Abstract: Background and Objectives: Surgical site infection (SSI) is a challenge for the surgeon. Incidence of SSI reported in literature varies from 0.5% to 15%. Severity of SSI ranges from superficial skin infection to life-threatening condition like septicaemia. It is responsible for increased morbidity, mortality, and economic burden to the hospital in general, and the patient in particular. The aim of this study was to assess the risk factors, bacteriological profile, length of hospitalization, and cost due to ort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…A review article on hospital-acquired infection from Singapore has reported that nosocomial infections are a significant issue worldwide, ranging from 5-10 % in European countries to more than 40% in Asia [ 29 ]. Like previous works increasing age, smoking, multiple co-morbidities, application of external fixator or wound closure at 1st surgery, failure to cover the wound within 5 days, higher Gustilo grade were significant risk factors for ultimate wound infection but alcoholism was not a risk factor in our analysis [ 30 , 31 ]. Our country has an extremely low rate of alcohol consumption [ 32 ].…”
Section: Discussionsupporting
confidence: 67%
“…A review article on hospital-acquired infection from Singapore has reported that nosocomial infections are a significant issue worldwide, ranging from 5-10 % in European countries to more than 40% in Asia [ 29 ]. Like previous works increasing age, smoking, multiple co-morbidities, application of external fixator or wound closure at 1st surgery, failure to cover the wound within 5 days, higher Gustilo grade were significant risk factors for ultimate wound infection but alcoholism was not a risk factor in our analysis [ 30 , 31 ]. Our country has an extremely low rate of alcohol consumption [ 32 ].…”
Section: Discussionsupporting
confidence: 67%
“…Advances in Orthopedics e incidence of orthopedic-related postoperative infections in the literature ranges from 2.5% to 41.9% [11,[16][17][18][19][20][21][22][23]. Comparable rates were found in developing countries, such that in a study conducted on 3096 orthopedic patients at a university hospital in Saudi Arabia, the incidence was found to be 2.55% [24].…”
Section: Discussionmentioning
confidence: 99%
“…7 The risk factors of SSI are patient-related (e.g., pre-existing infection, elderly age), procedure-related and operative environment-related (e.g., emergency surgery, inadequate antiseptic surgical site preparation, air quality of OT). 8,9 Surgery in patients with poly-trauma, hemodynamic instability and patients who develop postoperative hypothermia, hypoxia, hyperglycaemia are prone to develop SSI. 10 Surgical site infection (SSI) surveillance is an important part of hospital infection control practice.…”
Section: Introductionmentioning
confidence: 99%